Hubungan Pengetahuan Covid19 Dengan Perilaku Pencegahan Penularan Di Masa Pandemi Pada Siswa SMPN 1 Sekampung Udik Lampung Timur Tahun 2021 - Umi Romayati Keswara; Wahid Tri Wahyudi; Ade Gunawati Sandi (Malahayati Nursing Journal, 2021)
ABSTRACT: THE RELATIONSHIP OF COVID-19 KNOWLEDGE WITH TRANSMISSION PREVENTION BEHAVIOR IN PANDEMIC TIMES IN STUDENTS OF SMPN 1 SEKAMPUNG UDIK EAST LAMPUNG IN 2021. Introduction: Coronavirus Disease 2019 (COVID-19) is a new form of Coronavirus that causes an infectious disease. The number of persons infected with this virus is continuing to rise, and it can affect everyone from children to the elderly. Because there is currently no known remedy for this sickness, the government can only promote it by imposing a large-scale social restriction (PSBB) policing scheme. The impact of public awareness of Covid-19 and knowledge of health protocols on the PSBB's successful implementation cannot be separated. According to the results of a pre-survey done at SMPN 1 Sekampung Udik, East Lampung, which included an interview with one of the teachers, there were five teachers who tested positive for COVID-19 and There were still a lot of students who didn't follow the school's health regulations.Objective: To find out the relationship between knowledge of Covid-19 and transmission prevention behavior in students at SMPN 1 Sekampung Udik, East Lampung.Methods: This type of quantitative research was carried out at SMPN 1 Sekampung Udik, East Lampung, using an analytical observational research design using a cross sectional method. The participants in this study were all 651 students from SMPN 1 Sekampung Udik in East Lampung. With stratified random sampling and then accidental sampling, a minimum sample of 249 respondents was produced. Data was gathered through the use of a Google Forms questionnaire that was distributed to responders. The data was analyzed in two ways: univariate (frequency distribution) and bivariate (chi square).Results: Based on the results of statistical tests, it is known that 135 (54.2%) respondents with poor knowledge and 130 (52.2%) negative behavior. The p-value is 0.022, with an Odd Ratio of 1.862.Conclusion: There is a relationship between knowledge of covid-19 and behavior to prevent transmission during the pandemic for students of SMPN 1 Sekampung Udik, East Lampung in 2021. It is recommended for schools to further increase counseling about preventing transmission of covid-19 to students so as to minimize the incidence of covid-19. Keywords: knowledge, behavior, Covid-19INTISARI: HUBUNGAN PENGETAHUAN COVID-19 DENGAN PERILAKU PENCEGAHAN PENULARAN DI MASA PANDEMI PADA SISWA SMPN 1 SEKAMPUNG UDIK LAMPUNG TIMUR TAHUN 2021 Pendahuluan: Coronavirus Disease 2019 (COVID-19) ialah penyakit menular yang disebabkan oleh virus jenis baru. Peningkatan kasus oleh virus ini terus meningkat, berbagai masyarakat dari anak-anak sampai dengan lansia pun dapat terjangkit virus ini. Sampai dengan saat ini belum diketahui obat dari penyakit ini sehingga pemerintah hanya dapat melakukan upaya promotif dengan memberlakukan kebijakan pembatasan sosial berskala besar (PSBB). Berjalannya PSBB dengan baik tidak lepas dari pengaruh pengetahuan masyarakat tentang Covid-19 dan pengetahuan tentang protokol kesehatan. Berdasarkan hasil pra survey yang dilakukan di SMPN 1 Sekampung Udik Lampung Timur dengan mewawancarai salah satu guru didapatkan ada 5 guru yang sudah dinyatakan positif terjangkit COVID-19 dan masih banyak para siswa yang tidak mematuhi protokol kesehatan di sekolah.Tujuan: Diketahui hubungan antara pengetahuan Covid-19 dengan perilaku pencegahan penularan pada siswa di SMPN 1 Sekampung Udik Lampung Timur.Metode: Jenis penelitian kuantitatif, rancangan penelitian ini analytical observational dengan pendekatan cross sectional, telah dilakukan di SMPN 1 Sekampung Udik Lampung Timur. Populasi dalam penelitian ini adalah seluruh siswa SMPN 1 Sekampung Udik Lampung Timur yang berjumlah 651 siswa. Sampel minimum yang didapatkan berjumlah 249 responden dengan teknik stratified random sampling lalu accidental sampling. Pengambilan data menggunakan kuisioner google form yang dibagikan kepada responden. Analisa data secara univariat (distribusi frekuensi) dan bivariat (chi square).Hasil: Berdasarkan hasil uji statistik, diketahui 135 (54,2%) responden dengan pengetahuan tidak baik dan 130 (52,2%) perilaku negatif. Didapatkan p-value 0,022, dengan Odd Ratio 1,862.Kesimpulan: Ada hubungan antara pengetahuan covid-19 dengan perilaku pencegahan penularan di masa pandemi pada siswa SMPN 1 Sekampung Udik Lampung Timur Tahun 2021. Bagi pihak sekolah disarankan untuk lebih meningkatkan penyuluhan tentang pencegahan penularan covid-19 terhadap siswa sehingga dapat meminimalisir angka kejadian covid-19. Kata Kunci : pengetahuan, perilaku, Covid-19